The role of microRNAs in ferroptosis - Guo, Liqing; Zhang, Qingkun; Liu, Yuehui (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a newly discovered type of programmed cell death, which is closely related to the imbalance of iron metabolism and oxidative stress. Ferroptosis has become an important research topic in the fields of cardiomyopathy, tumors, neuronal injury disorders, and ischemia perfusion disorders. As an important part of non-coding RNA, microRNAs regulate various metabolic pathways in the human body at the post-transcriptional level and play a crucial role in the occurrence and development of many diseases. The present review introduces the mechanisms of ferroptosis and describes the relevant pathways by which microRNAs affect cardiomyopathy, tumors, neuronal injury disorders and ischemia perfusion disorders through regulating ferroptosis. In addition, it provides important insights into ferroptosis-related microRNAs, aiming to uncover new methods for treatment of the above diseases, and discusses new ideas for the implementation of possible microRNA-based ferroptosis-targeted therapies in the future.